The Approach of Traditional Persian Medicine to Treatment of Anal Fissure - Ghazaleh Mosleh; Majid Nimrouzi; Parmis Badr; Zohreh Abolhasanzadeh; Amir Azadi; Abdolali Mohagheghzadeh (Traditional and Integrative Medicine, 2019)
The common disorder of anal fissure is a painful linear crack in lining of anus. So-called Shiqaq-e-maghad in Persian medical manuscripts has different etiologically-oriented therapies. The aim of this study was to describe the therapeutic guideline for anal fissure in Persian Medicine. Six manuscripts including al-Hawi fi al-Tibb, Qanun fi-Tibb, Qarabadin Kabir, Tibb Akbari, Makhzan-al-Adviah and Exir-e Azam were searched using the keyword of Shiqaq-e-maghad. Although the exact etiology of anal fissure is still uncertain, it has been suggested that a local trauma may cause spasm in internal sphincter of anus leading to a local ischemia and anal fissure. Based on traditional viewpoint, dystemperament, defecation problem, hemorrhoid, inflammation, fullness of veins, and trauma are reasons of anal fissure needing four types of medication including anti-inflammatory drugs, emollients, wound healing agents, and selective remedies. Considering neglected points of traditional outlook will broaden the paths to cure anal fisher.